The Role of Mosque Youth Association Leadership Management in Improving Member Performance NuruL Hikmah Mosque - Thariq Aziz; Abdul Kosim; Kasja Eki Waluyo (Edumaspul: Jurnal Pendidikan, 2022)
The youth association of the mosque is a forum or place for organizations to study Islam, cultivate religious morals, through habits such as recitation, da'wah and reading the Koran as an effort to guide religious understanding for generations of the nation who are often referred to as teenagers. Therefore, the group is often called the mosque youth association. One of them is in the Nurul Hikmah mosque in Purwadana village. The purpose of doing this research is none other than to find out how influential the current chairman's leadership is in terms of improving the performance of its members. The research method that the author uses is a qualitative research in which the author conducts direct observations and interviews with the resource person, namely the chairman of IRMANUH at his residence. The results obtained indicate that it is true that during this pandemic the spirit and performance of each member decreased due to restrictions on direct and crowding activities and were not accustomed to online activities, so it could be interpreted that the management experienced a lack of understanding of online activities. The role of a leader in an organization is so great in improving the performance of its members, because after all now is a difficult time for any organization because the covid pandemic always mutates into several variants that contain activities directly and involve many calls to be limited by the government.